Stacked body and hard coating agent
Patent Information
- Application Number
- CN202611344240.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-02-04
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-23
AI Technical Summary
但是,该膜难以兼顾密合性、耐热性、硬度、耐擦伤性的特性
[0034]根据本公开,能够提供具有即使在冷热循环试验后与丙烯酸系基材的密合性、硬度和耐擦伤性也优异的硬涂层、且干涉不均得到抑制的层叠体。另外,能够提供用于形成这样的硬涂层的硬涂剂。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This disclosure relates to laminates and hard coatings. Background Technology
[0002] In various displays used as image display devices such as LCDs, plasma displays, EL displays, rear projection displays, and CRT displays in televisions, computers, car navigation systems, vehicle dashboards, and mobile phones, a laminate with a substrate and a hard coating (hereinafter sometimes simply referred to as a hard coating film) is used for the purpose of protecting the surface of the display.
[0003] Hard coatings require excellent mechanical properties, dimensional stability, and electrical insulation. However, besides optical display materials such as monitors, they can also be used in various applications such as packaging materials, electrical insulation materials, various photographic materials, and graphic arts materials. Therefore, transparent plastics are mostly used as the substrate. Among transparent plastics, and in optical display materials such as monitors, triacetyl cellulose (TAC) films are often used due to their transparency, refractive index, impact resistance, heat resistance, and durability.
[0004] However, TAC membranes are highly permeable and hygroscopic. Therefore, in high-temperature and / or high-humidity environments, the membrane's dimensions may change due to moisture absorption, leading to deformation or reduced adhesion to the hard coating. In recent years, acrylic substrates have begun to be used as substrates that can withstand these problems. However, when using acrylic substrates, problems sometimes arise regarding adhesion to the hard coating, hardness, abrasion resistance, and heat resistance (especially adhesion after thermal cycling tests).
[0005] Patent Document 1 discloses an active energy ray curable resin composition containing a urethane (meth)acrylate resin, a (meth)acrylate compound having one or more and two (meth)acryloyl groups in one molecule, and a (meth)acrylate compound having three or more (meth)acryloyl groups in one molecule.
[0006] However, for films comprising a hard coating formed from this composition and an acrylic substrate, adhesion sometimes decreases after thermal cycling tests, making it difficult to achieve both excellent adhesion and hardness. Furthermore, interference of light at the interface between the hard coating and the substrate causes uneven interference (iron-colored unevenness), resulting in insufficient visual recognition when used in displays. In addition, it also damages the aesthetics of the display.
[0007] Patent Document 2 discloses a laminate formed by laminating an acrylic film for UV embossing with an uneven shape on at least one surface of an acrylic film (I) and a haze of 1% or more with a UV-curable resin. However, this laminate has problems with heat resistance, such as shape changes caused by heat.
[0008] Patent document 3 discloses a film comprising a micro-textured surface and a heat-resistant acrylic film. However, this film struggles to simultaneously achieve properties such as adhesion, heat resistance, hardness, and scratch resistance.
[0009] Patent document 4 discloses an acrylic film with excellent surface hardness, toughness, UV absorption capacity, durability, and optical isotropy. However, this film is difficult to simultaneously achieve properties such as adhesion, heat resistance, hardness, and scratch resistance.
[0010] Existing technical documents
[0011] Patent documents
[0012] Patent Document 1: International Publication No. 2020 / 209264
[0013] Patent Document 2: Japanese Patent Application Publication No. 2010-196026
[0014] Patent Document 3: Japanese Patent Application Publication No. 2013-137485
[0015] Patent Document 4: Japanese Patent Application Publication No. 2009-052036 Summary of the Invention
[0016] The problem that the invention aims to solve
[0017] The problem to be solved by this disclosure is to provide a laminate having a hard coating that exhibits excellent adhesion to an acrylic substrate, hardness, and scratch resistance even after thermal cycling tests, and where interference non-uniformity is suppressed. Additionally, a hardening agent for forming such a hard coating is provided.
[0018] Solution for solving the problem
[0019] In order to solve the above-mentioned problems, the inventors have conducted repeated and in-depth research, and as a result, the following invention has been completed. This disclosure provides a laminate formed from the following hardening agent, and the hardening agent.
[0020] [1] A laminate comprising a substrate and a hard coating, wherein the substrate is an acrylic substrate having a temperature of 125°C or higher and 160°C or lower at the peak of tanδ obtained by dynamic viscoelasticity determination at a frequency of 0.1 Hz, and the hard coating is formed by a hard coating agent comprising a compound (A) having 6 or more (meth)acryloyl groups, a compound (B) having 1 olefin unsaturated group, and a compound (C) having a silsesquioxane skeleton.
[0021] [2] In the above-described laminate, the above-described compound (B) is a compound having one (meth)acryloyl group.
[0022] [3] In the above-mentioned laminate, the above-mentioned compound (B) is a compound having one olefinic unsaturated group and a hydroxyl group.
[0023] [4] In the above-mentioned laminate, the above-mentioned compound (A) comprises a carbamate (meth)acrylate (a1) having 6 or more (meth)acryloyl groups.
[0024] [5] In the above-mentioned laminate, the hard coating also contains alumina particles.
[0025] [6] In the above-described laminate, the content of compound (A) is 20% or more and 55% or less in 100% by mass of the total of compound (A), compound (B) and compound (C), the content of compound (B) is 35% or more and 70% or less in 100% by mass of the total of compound (A), compound (B) and compound (C), and the content of compound (C) is 1% or more and 30% or less in 100% by mass of the total of compound (A), compound (B) and compound (C).
[0026] [7] A hard coating agent comprising a compound (A) having six or more (meth)acryloyl groups, a compound (B) having one olefinic unsaturated group, and a compound (C) having a silsesquioxane skeleton, wherein the compound (A) is a urethane (meth)acrylate having six or more (meth)acryloyl groups, the compound (B) is a compound having one (meth)acryloyl group, and the compound (C) is a compound having a silsesquioxane skeleton.
[0027] [8] A hard coating agent comprising a compound (A) having six or more (meth)acryloyl groups, a compound (B) having one olefin unsaturated group, and a compound (C) having a silsesquioxane skeleton, wherein the compound (A) is a urethane (meth)acrylate having six or more (meth)acryloyl groups, the compound (B) is a compound having one olefin unsaturated group and a hydroxyl group, and the compound (C) is a compound having a silsesquioxane skeleton.
[0028] [9] In the above-mentioned hard coating agent, the content of the above-mentioned compound (A) is 20% or more and 55% or less in the total of 100% by mass of the above-mentioned compound (A), the above-mentioned compound (B) and the above-mentioned compound (C).
[0029]
[10] In the above-mentioned hard coating agent, the content of the above-mentioned compound (B) is 40% by mass or more in the total of 100% by mass of the above-mentioned compound (A), the above-mentioned compound (B) and the above-mentioned compound (C).
[0030]
[11] In the above-mentioned hard coating agent, the content of the above-mentioned compound (C) is 1% or more and 20% or less of the total 100% by mass of the above-mentioned compound (A), the above-mentioned compound (B) and the above-mentioned compound (C).
[0031]
[12] In the above-mentioned hard coating agent, the content of the above-mentioned compound (A) is 20% or more and 55% or less in 100% by mass of the total of the above-mentioned compound (A), the above-mentioned compound (B) and the above-mentioned compound (C), the content of the above-mentioned compound (B) is 35% or more and 70% or less in 100% by mass of the total of the above-mentioned compound (A), the above-mentioned compound (B) and the above-mentioned compound (C), and the content of the above-mentioned compound (C) is 1% or more and 30% or less in 100% by mass of the total of the above-mentioned compound (A), the above-mentioned compound (B) and the above-mentioned compound (C).
[0032]
[13] The above-mentioned hard coating agent is used to form a hard coating in a laminate having an acrylic substrate and a hard coating, wherein the temperature at the peak of the tanδ obtained by dynamic viscoelasticity measurement at a measurement frequency of 0.1 Hz is 125°C or higher and 160°C or lower.
[0033] Invention Effects
[0034] According to this disclosure, a laminate with a hard coating exhibiting excellent adhesion to an acrylic substrate, hardness, and scratch resistance even after thermal cycling tests, and with interference non-uniformity suppressed, can be provided. Furthermore, a hard coating agent for forming such a hard coating can be provided. Detailed Implementation
[0035] The present disclosure will now be described in detail. Furthermore, other embodiments are naturally included within the scope of this disclosure as long as they conform to its spirit. In this specification, the numerical range defined by "~" is defined as the range of values before and after "~" as the lower and upper limits.
[0036] First, let me explain the terminology used in this instruction manual.
[0037] When expressed as "(meth)acrylic acid", "(meth)acryloyl", "(meth)acrylate", "(meth)acrylamide", or "(meth)acryloyl group", unless otherwise specified, they refer to "acrylic acid or methacrylic acid", "acryloyl or methacryloyl", "acrylate or methacrylate", "acrylamide or methacrylamide", or "acryloyl group or methacryloyl group", respectively.
[0038] Sometimes, the compound (A) having 6 or more (meth)acryloyl groups is simply referred to as "compound (A)", the carbamate (meth)acrylate (a1) having 6 or more (meth)acryloyl groups is simply referred to as "compound (a1)", the carbamate acrylate (a1-1) in synthesis example A1 is simply referred to as "compound (a1-1)", the carbamate acrylate (a1-2) in synthesis example A2 is simply referred to as "compound (a1-2)", the compound (a2) having 6 or more (meth)acryloyl groups other than compound (a1) is simply referred to as "compound (a2)", dipentaerythritol hexaacrylate is simply referred to as "compound (2-1)" or "DPHA", the compound (B) having 1 olefin unsaturated group is simply referred to as "compound (B)", 4-hydroxybutyl acrylate is simply referred to as "compound (b1)" or "HBA", and 3-hydroxybutyl acrylate is simply referred to as "compound (b1)". The following are abbreviations for compound (b2) or HPA: methylpropyl ester; compound (c1) with a sesquioxane skeleton and methacryloyl group; compound (c2) with a sesquioxane skeleton and acryloyl group; compound (c3) with a sesquioxane skeleton but no methacryloyl group; compound (d2) with two or more but less than five methacryloyl groups; ethylene oxide-modified triacrylate isocyanurate (d1); ethylene oxide-modified diacrylate isocyanurate (d2); and Aronix M315 is abbreviated as M315.
[0039] In addition, dynamic viscoelasticity measurement is sometimes abbreviated as "DMA", differential scanning calorimetry as "DSC", glass transition temperature as "Tg", number-average molecular weight as "Mn", and weight-average molecular weight as "Mw". Furthermore, these physical property values can be measured according to the methods disclosed in the examples.
[0040] Sometimes, "active energy ray curable hard coating" is simply referred to as "hard coating". Unless otherwise specified, the components contained in hard coatings, hard coatings, and substrates can be used independently or in combination of two or more.
[0041] [Layered Body]
[0042] The laminate of this disclosure (sometimes also referred to as the laminate) is characterized by having a substrate and a hard coating layer. The substrate is an acrylic substrate with a temperature of 125°C or higher and 160°C or lower at the peak of tanδ obtained by dynamic viscoelasticity determination at a measurement frequency of 0.1 Hz. The hard coating layer is formed of a hard coating agent comprising a compound (A) having 6 or more (meth)acryloyl groups, a compound (B) having 1 olefin unsaturated group, and a compound (C) having a silsesquioxane skeleton.
[0043] This laminate can be used for a variety of applications, including: display panels (e.g., liquid crystal displays), touch screen panels (e.g., mobile phones, smartphones, tablets, laptops), semiconductor components, printed circuit boards and other electronic devices; laminates (e.g., glass products, films or sheets) used in buildings, residences and other constructions, ships, aircraft and automobiles and other vehicles, industrial applications, optical applications, solar cell panels, food packaging and other applications; and glass products used in beakers, flasks, tableware and other applications.
[0044] [Acrylic substrate]
[0045] From the viewpoint of improving adhesion to the hard coating and suppressing interference inhomogeneity, the substrate used in this laminate is an acrylic substrate with a peak tanδ temperature of 125°C or higher and 160°C, obtained by dynamic mechanical analysis (DMA) at a measurement frequency of 0.1 Hz. A representative acrylic substrate is methyl methacrylate homopolymer, whose peak tanδ temperature does not significantly exceed its glass transition temperature of 105°C even after stretching. For example, it can be obtained by film-forming methyl methacrylate copolymer granules as described below under the following conditions, stretching them, and then subjecting them to heat-fixing treatment (hereinafter sometimes referred to as stretching). The molecular orientation of the methyl methacrylate copolymer film with a peak tanδ temperature of 125°C or higher and 160°C after stretching is improved, which does not reduce the adhesion to the hard coating improved by (meth)acrylate compounds having only one (meth)acrylyl group per molecule, and can suppress shape changes (shrinkage, etc.) caused by heat.
[0046] <Methyl methacrylate copolymer granules>
[0047] When copolymerized with methyl methacrylate, copolymers with high glass transition temperatures can be expected. Examples of monomers include acrylic acid (glass transition temperature of homopolymer 228°C) and isobornyl methacrylate (glass transition temperature of homopolymer 155°C). From the perspective of reactivity and affinity close to methyl methacrylate, α-hydroxymethyl methacrylate and α-methyl-γ-butyrolactone are preferred monomers for copolymerization with methyl methacrylate. As methyl methacrylate copolymer granules, commercially available products such as Acryviewa TRM-Z-100 (trade name, manufactured by Nippon Shokubai Co., Ltd., methyl methacrylate-α-hydroxymethyl methacrylate copolymer, Tg 122°C) and Acryviewa TRM-250 (trade name, manufactured by Nippon Shokubai Co., Ltd., methyl methacrylate-α-hydroxymethyl methacrylate copolymer, Tg 130°C) can be used. Alternatively, granules can be obtained by separating, washing, drying, and granulating a copolymer obtained by suspension copolymerization of methyl methacrylate and α-methyl-γ-butyrolactone. The Tg can be adjusted by the polymerization ratio of methyl methacrylate to α-methyl-γ-butyrolactone.
[0048] <Glass transition temperature of methyl methacrylate copolymer granules>
[0049] The glass transition temperature of methyl methacrylate copolymer granules was determined using a differential scanning calorimetry (DSC) at a heating rate of 20 °C / min. The glass transition temperature Tg at the midpoint was calculated according to JIS-K7121 (1987).
[0050] <Film Formation of Methyl Methacrylate Copolymer Particles>
[0051] Methyl methacrylate copolymer granules are fed into a biaxial melt mixer with a T-die, and melt-formed at a temperature higher than the glass transition temperature (Tg) of the granules. The resulting film, obtained by adjusting the winding speed, is fed into an automatic biaxial stretching device, where it is simultaneously biaxially stretched 1.5 times at a temperature higher than Tg to obtain a film of a specified average thickness. The biaxial stretching temperature is preferably 5°C or higher and 50°C or lower than Tg, more preferably 10°C or higher and 40°C or lower, and even more preferably 15°C or higher and 30°C or lower.
[0052] <Peak temperature of the loss coefficient tanδ of the dynamic viscoelasticity of methyl methacrylate copolymer films>
[0053] According to JIS K7244-4, using a DMA measuring instrument, the loss coefficient tanδ is measured at a measurement frequency of 0.1Hz, and its peak temperature is determined.
[0054] The peak temperature of the loss coefficient tanδ of the dynamic viscoelasticity of the membrane represents the glass transition temperature that captures the mechanical changes of the membrane, but shows a different value from the glass transition temperature (Tg) obtained above using differential scanning calorimetry (DSC).
[0055] The temperature at the peak of tanδ is preferably 125°C or higher, more preferably 130°C or higher, and even more preferably 135°C or higher. By setting the temperature at the peak of tanδ to 125°C or higher, the thermal dimensional stability of the acrylic substrate is improved, and the adhesion between the hard coating and the acrylic substrate after thermal cycling tests is enhanced. Furthermore, the temperature at the peak of tanδ is preferably 160°C or lower, more preferably 155°C or lower, and even more preferably 150°C or lower. By setting the temperature at the peak of tanδ to 160°C or lower, the adhesion (initial adhesion) between the hard coating and the acrylic substrate is improved. The temperature at the peak of tanδ can be 125°C or higher and 160°C or lower, 130°C or higher and 155°C or lower, or 135°C or higher and 150°C or lower.
[0056] The thickness of the substrate is not particularly limited, but is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 15 μm or more. Furthermore, the thickness of the substrate is preferably 100 μm or less, more preferably 80 μm or less, and even more preferably 60 μm or less. It can be 5 μm or more and 100 μm or less, 10 μm or more and 80 μm or less, or 15 μm or more and 60 μm or less. In this disclosure, the thickness of the substrate is the arithmetic mean of the thicknesses measured at any five points on the substrate.
[0057] [Hard coating]
[0058] The hard coating is formed from a hard coating agent comprising a compound (A) having more than 6 (meth)acryloyl groups, a compound (B) having 1 olefin unsaturated group, and a compound (C) having a sesquioxane skeleton.
[0059] The dried film thickness of the hard coating is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 3 μm or more. Furthermore, the dried film thickness is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. It can be 1 μm or more and 20 μm or less, 2 μm or more and 15 μm or less, or 3 μm or more and 10 μm or less. In this disclosure, the dried thickness of the hard coating is calculated by measuring the thickness of any five points of the hard coating and using the arithmetic mean of these measurements.
[0060] [Compound (A)]
[0061] Compound (A) is a compound having six or more (meth)acryloyl groups. The (meth)acryloyl groups in compound (A) can be 6–30, 6–20, 6–15, or 6–10. From the viewpoint of pencil hardness and scratch resistance, the (meth)acryloyl groups in compound (A) can be 6–10, 6–9, or 6–8. From the viewpoint of tightness, the (meth)acryloyl groups in compound (A) can be 10–20, 10–15, or 10–12. In compound (A), the multiple (meth)acryloyl groups can all be the same methacryloyl group or acryloyl group, or they can be a combination of both.
[0062] The hard coating may contain one or more compounds (A). When using two or more compounds (A), compounds (A) with different numbers of (meth)acryloyl groups may be used. For example, compounds (A) with 10 or less, 6 to 10, 6 to 9, or 6 to 8 (meth)acryloyl groups may be used in combination with compounds (A) with 10 to 20, 10 to 15, or 10 to 12 (meth)acryloyl groups.
[0063] Compound (A) can be exemplified by: polyols having 6 or more (meth)acryloyl groups, esters of (meth)acrylic acid, urethane acrylates, polyester acrylates, epoxy acrylates, acrylates having a urethane ring skeleton, etc., but is not limited to these.
[0064] Compound (A) may comprise a urethane (meth)acrylate (a1) having six or more (meth)acryloyl groups (compound (a1)), a compound (a2) having six or more (meth)acryloyl groups other than compound (a1), or a combination thereof.
[0065] When compound (A) comprises a combination of compound (a1) and compound (a2), the mass ratio of compound (a1) to the total mass of compound (a1) and compound (a2) can be 10 to 40% by mass, 15 to 35% by mass, or 20 to 30% by mass.
[0066] Examples of compounds (a1) include compounds obtained by reacting polyisocyanates with hydroxyl-containing (meth)acrylates, compounds obtained by reacting polyols with polyisocyanates under conditions of excess isocyanate groups with hydroxyl-containing urethane prepolymers, and compounds obtained by reacting polyols with polyisocyanates under conditions of excess hydroxyl groups with hydroxyl-containing urethane prepolymers.
[0067] Compound (a1) can be obtained by stirring a polyisocyanate and a hydroxyl-containing (meth)acrylate in the presence of a suitable carbamate catalyst under an oxygen atmosphere at 60–100 °C for 4–8 hours.
[0068] Specific examples of the aforementioned carbamate esterification catalysts include copper naphthenate, cobalt naphthenate, zinc naphthenate, dibutyltin dilaurate, triethylamine, 1,4-diazabicyclo[2.2.2]octane, and 2,6,7-trimethyl-1,4-diazabicyclo[2.2.2]octane. Among these, dibutyltin dilaurate is preferred as the carbamate esterification catalyst.
[0069] Examples of the polyisocyanates used in the manufacture of compound (a1) include aliphatic diisocyanates and aromatic diisocyanates.
[0070] Examples of aliphatic diisocyanates include hexamethylene diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethylene diisocyanate, and hydrogenated diphenylmethane diisocyanate.
[0071] Examples of the aforementioned aromatic diisocyanates include toluene diisocyanate, phenylene diisocyanate, and diphenylmethane diisocyanate. It should be noted that the bonding position between the isocyanate group and the aromatic group can be any of the ortho, meta, or para positions. Furthermore, this diisocyanate can form an isocyanurate ring in the form of a trimer.
[0072] From the perspective of suppressing yellowing when envisioning optical applications, aliphatic diisocyanates are preferred among the aforementioned polyisocyanates. Polyisocyanates can be used alone or in combination of two or more.
[0073] From the viewpoint of hardness and scratch resistance, the aforementioned hydroxyl-containing (meth)acrylates used in the manufacture of compound (a1) are preferably (meth)acrylates having three or more (meth)acryloyl groups and hydroxyl groups. Specifically, pentaerythritol tri(meth)acrylate and dipentaerythritol penta(meth)acrylate are preferred. They can be used alone or in combination of two or more.
[0074] The number-average molecular weight (Mn) of compound (a1) is preferably 500 or more, more preferably 600 or more, further preferably 700 or more, and even more preferably 800 or more. Furthermore, Mn is preferably 5500 or less, more preferably 5000 or less, further preferably 4500 or less, and even more preferably 4000 or less. Mn can be 500 or more and 5500 or less, 600 or more and 5000 or less, 700 or more and 4500 or less, or 800 or more and 4000 or less. If Mn is 500 or more, the adhesion is further improved. Furthermore, if Mn is 5500 or less, the hardness and scratch resistance are further improved. When two or more compounds (A) are used together, it is preferable that the Mn of all compounds (a1) is within the above-mentioned range.
[0075] The Mn of compound (a1) can be adjusted by a combination of various materials used in the manufacture of compound (A), namely polyols, polyisocyanates and hydroxyl-containing mono(meth)acrylates or poly(meth)acrylates.
[0076] Compound (a2) is a compound other than compound (a1) that has six or more (meth)acryloyl groups. Compound (a2) can be manufactured using polyols and (meth)acrylic acid esters, polyester (meth)acrylates, polyepoxy (meth)acrylates, and other multifunctional (meth)acrylate resins.
[0077] Examples of polyol-(meth)acrylic acid ester compounds include dipentaerythritol hexa(meth)acrylate, alkyl-modified dipentaerythritol hexa(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate.
[0078] Polyester (meth)acrylates can be obtained, for example, by reacting polyester polycarboxylic acids, obtained by polycondensation of polybasic acids and polyols, with hydroxyl-containing (meth)acrylates.
[0079] Examples of polycarboxylic acids include aliphatic polycarboxylic acids, alicyclic polycarboxylic acids, and aromatic polycarboxylic acids. For instance, examples of aliphatic polycarboxylic acids include oxalic acid, malonic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, octanoic acid, maleic acid, fumaric acid, dodecanoic acid, pimelic acid, citraconic acid, glutaric acid, itaconic acid, succinic anhydride, and maleic anhydride; their aliphatic dicarboxylic acids and their anhydrides can be utilized. Alternatively, derivatives of the anhydrides can also be used.
[0080] In addition, examples of the aforementioned polyols include ethylene glycol and propylene glycol. (glycol), dipropylene glycol, diethylene glycol, triethylene glycol, butanediol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 2-methyl-1,8-octanediol, 3,3'-dihydroxymethylheptane, 2-butyl-2-ethyl-1,3-propanediol, polyethylene glycol (addition molar number less than 10), polyoxypropylene glycol (addition molar number less than 10), propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, neopentanediol, octanediol, butylethylpentanediol, 2-ethyl-1,3-hexanediol, cyclohexanediol, cyclohexanediol, tricyclodecanediol, cyclopentadienediol, dimerols, and other aliphatic or alicyclic diols.
[0081] In addition, examples of polyols having three or more hydroxyl groups include glycerol, trimethylolpropane, pentaerythritol, and dipentaerythritol.
[0082] Among the aforementioned polyols, from the perspective of compatibility, neopentyl glycol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 2-methyl-1,8-octanediol, 3,3'-dihydroxymethylheptane, 2-butyl-2-ethyl-1,3-propanediol, butylethylpentanediol, 2-ethyl-1,3-hexanediol, and trimethylolpropane are preferred, as they have two or more hydroxyl groups on the branched aliphatic hydrocarbon groups.
[0083] Examples of (meth)acrylates having hydroxyl groups include the same (meth)acrylates as described above, among which trimethylolpropane di(meth)acrylate, trimethylolethane di(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol penta(meth)acrylate are preferred.
[0084] Examples of poly(meth)acrylates include substances in which the glycidyl groups of an epoxy resin are esterified with (meth)acrylic acid to make the functional groups (meth)acrylate groups.
[0085] Examples of (meth)acrylates having an isocyanurate ring backbone include the reaction product of isocyanurate trimer of diisocyanate with poly(meth)acrylate compound having hydroxyl group, and the reaction product of isocyanurate trimer of polyisocyanate with polyol and poly or mono(meth)acrylate compound having hydroxyl group.
[0086] The content of compound (A) is preferably 20% by mass or more, more preferably 25% by mass or more, and even more preferably 30% by mass or more, out of a total of 100% by mass of compounds (A), (B), and (C). Furthermore, the content of compound (A) is preferably 55% by mass or less, more preferably 50% by mass or less, and even more preferably 45% by mass or less. It can be 20% by mass or more and 55% by mass or less, 25% by mass or more and 50% by mass or less, or 30% by mass or more and 45% by mass or less. By achieving the above-mentioned content, the hardness, scratch resistance, and adhesion are further improved.
[0087] Compound (A) can be used alone or in combination with two or more compounds. From the viewpoint of hardness and adhesion, it is preferable to use two or more compounds (A) in combination. For example, combinations of compounds (a1) and (a2) mentioned above, or combinations of two or more compounds (A) with different numbers of (meth)acryloyl groups can be given.
[0088] [Compound (B)]
[0089] Compound (B) is a compound having one olefinically unsaturated group. The binding affinity is further improved by including compound (B). An olefinically unsaturated group refers to a group containing a carbon-carbon double bond; specifically, examples include vinyl, allyl, acryloyl, and methacryloyl groups. Acryloyl and methacryloyl groups are preferred examples.
[0090] Examples of compounds (B) include: methyl methacrylate, ethyl methacrylate, lauryl methacrylate, and other alkyl methacrylates; isobornyl methacrylate and other cycloalkyl methacrylates; polyalkylene glycol monoalkyl ether methacrylates such as methoxy polyethylene glycol methacrylate; benzyl methacrylate, phenoxyethyl methacrylate, and other methacrylates containing aromatic rings; 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 4-hydroxybutyl methacrylate, and other hydroxyalkyl methacrylates; phosphorus-containing alkyl methacrylates such as 2-(meth)acryloyloxyethyl phosphate; styrene, α-methylstyrene, and other styrene. Compounds containing methacryloyl groups; γ-(meth)acryloyloxypropyltrimethoxysilane, γ-(meth)acryloyloxypropyltriethoxysilane, etc. (meth)acryloyloxytrialkoxysilanes; N,N-dialkylaminoalkyl (meth)acrylamides such as 2-(N,N-dimethylamino)ethyl methacrylate; alkyl (meth)acrylamides such as diethyl (meth)acrylamides; hydroxyalkyl (meth)acrylamides such as N-hydroxymethyl (meth)acrylamides; lactams containing (meth)acryloyl groups such as N-vinyl-ε-caprolactam; nitrogen-containing cyclic compounds containing (meth)acryloyl groups such as (meth)acryloylmorpholine; fluorinated alkyl esters such as trifluoroethyl (meth)acrylate, 2,2,3,3,3-pentafluoropropyl (meth)acrylate; and silicone compounds with a terminal (meth)acryloyl group, etc.
[0091] From the perspective of adhesion, compound (B) is preferably a compound having one olefinic unsaturated group and a hydroxyl group. In this case, the hydroxyl group contained in compound (B) can be 1 to 4, 1 to 3, 1 to 2, or 1, preferably 1. Furthermore, the hydroxyl group contained in compound (B) can be in the form of a hydroxyalkyl group, and the number of carbon atoms in the hydroxyalkyl group is preferably 1 to 8, 2 to 6, or 3 to 4. From the perspective of adhesion, hydroxyalkyl (meth)acrylate is more preferred, 4-hydroxybutyl acrylate or hydroxypropyl acrylate are even more preferred, and 4-hydroxybutyl acrylate is particularly preferred.
[0092] The content of compound (B) is preferably 35% by mass or more and 70% by mass or less, more preferably 40% by mass or more and 65% by mass or less, and even more preferably 45% by mass or more and 60% by mass or less, within the total 100% by mass of compounds (A), (B), and (C). By achieving the above-mentioned content, a balance can be achieved in terms of hardness, scratch resistance, sealing performance, and sealing performance after thermal cycling tests.
[0093] [Compound (C)]
[0094] Compound (C) is a compound with a silsesquioxane framework. The rigid framework of the silsesquioxane framework results in good hardness and scratch resistance in the hard coating.
[0095] Compound (C) is any sesquioxane, i.e., obtained by hydrolysis and condensation of a trifunctional silane, possessing (RSiO) 1.5 ) n There are no particular limitations on the type of polymer, such as network polymers or compounds with polyhedral cluster structures; compounds with silsesquioxane skeletons, such as random structures, ladder structures, fully cage structures, and incomplete cage structures, can be used. (RSiO) 1.5 ) n In this context, n is an integer of 2 or more. n is preferably 200 or less, more preferably 150 or less, and even more preferably 100 or less. It can be 2 to 200, 2 to 150, or 2 to 100. Additionally, (RSiO 1.5 ) n In this context, R is preferably an organic residue such as methyl, ethyl, phenyl, or (meth)acryloyl.
[0096] Compound (C) can be broadly classified into (RSiO) 1.5 ) n Compound (c1) is a compound having a silsesquioxane skeleton and a methacryloyl group, at least a portion of R being (meth)acryloyl; compound (c2) has a silsesquioxane skeleton and a methacryloyl group; and compound (c3) has a silsesquioxane skeleton but no (meth)acryloyl group. Compound (C) preferably includes compound (c1) or compound (c2). By including compound (c1) or compound (c2), the reduction in hardness of the hard coating can be further suppressed. It should be noted that even compounds with a silsesquioxane skeleton that have 6 or more (meth)acryloyl groups are not within the scope of compound (A) but fall within the scope of compound (C). Furthermore, even compounds with a silsesquioxane skeleton that have one olefin unsaturated group, for example, even if the olefin unsaturated group is (meth)acryloyl, are not within the scope of compound (B) but fall within the scope of compound (C).
[0097] Commercially available examples of compounds (c1) and (c2) include AC-SQ TA-100, MAC-SQ TM-100, AC-SQ SI-20, MAC-SQ SI-20, and MAC-SQ HDM manufactured by Toa Synthetic Co., Ltd. Commercially available examples of compounds (c3) include SR-21, SR-23, SR-13, SR-33, and SO-04 manufactured by Konishi Chemical Industry Co., Ltd.; SQ 107, SQ 109, and SQ 506 manufactured by Arakawa Chemical Industry Co., Ltd.; and OX-SQ TX-100, OX-SQ SI-20, and OX-SQ HDX manufactured by Toa Synthetic Co., Ltd.
[0098] The content of compound (C) is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, out of a total of 100% by mass of compounds (A), (B), and (C). Furthermore, the content of compound (C) is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less. It can be 1% by mass or more and 30% by mass or less, 2% by mass or more and 20% by mass or less, or 3% by mass or more and 10% by mass or less. With the above-mentioned content, the hardness is high, and interference of light reflected at the interface between the hard coating and the acrylic substrate can be further suppressed, therefore it is preferred. In addition, the adhesion after cyclic testing is also improved.
[0099] [Hard coating]
[0100] The hard coating agent of the present invention comprises a compound (A) having six or more (meth)acryloyl groups, a compound (B) having one olefinic unsaturated group, and a compound (C) having a silsesquioxane skeleton. Preferably, compound (A) is a urethane (meth)acrylate having six or more (meth)acryloyl groups, and compound (B) is a compound having one olefinic unsaturated group and a hydroxyl group. To facilitate coating of the substrate, the hard coating agent of this disclosure preferably contains a solvent such as an organic solvent.
[0101] [Organic solvents]
[0102] As organic solvents, aromatic organic solvents such as toluene and xylene; ketone organic solvents such as methyl ethyl ketone (sometimes abbreviated as "MEK") and methyl isobutyl ketone; ester organic solvents such as ethyl acetate, propyl acetate, isopropyl acetate, and isobutyl acetate; alcohol organic solvents such as methanol, ethanol, propanol, isopropanol, and butanol; and glycol ether organic solvents such as propylene glycol monomethyl ether are all known organic solvents. When organic solvents are included, from the viewpoint of coatability and film-forming properties, the concentration of non-volatile components in the hard coating agent disclosed herein is preferably 1% by mass or more and 75% by mass or less, more preferably 5% by mass or more and 70% by mass or less, and even more preferably 10% by mass or more and 65% by mass or less.
[0103] The hard coating agent disclosed herein can be manufactured as long as it can be mixed uniformly. For example, it can be manufactured by mixing compounds (A), (B), and (C) with the required organic solvent using a mixer (dispersant), homogenizer, etc. In cases where the hard coating agent, such as alumina particles, contains insoluble components, it can be dispersed using a roller mill, sand mill, gamma mill, etc.
[0104] When using the hard coating agent of this disclosure to manufacture the laminate of this disclosure, it can be manufactured by conventional methods such as coating the hard coating agent onto an acrylic substrate. For example, the following method can be used: after coating the hard coating agent onto the acrylic substrate, heat drying is performed as needed to evaporate the solvent, and the coated hard coating layer is further cured by irradiation with active energy rays.
[0105] Examples of coating methods include bar coating, blade coating, spin coating, reverse coating, mold coating, spray coating, roller coating, gravure coating, micro-gravure coating, lip coating, air knife coating, and impregnation.
[0106] Examples of active energy rays include electron beams and light emitted from sources such as xenon lamps, low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, carbon arc lamps, and tungsten lamps.
[0107] [Alumina particles]
[0108] The hard coating and hard coating agent preferably contain alumina particles.
[0109] The preferred alumina particles have a θ-type and / or α-type crystal structure, with a primary particle size of 5 nm or more and 100 nm or less. This is to reduce haze and coloration in the hard coating. Here, primary particle size refers to the size of the particles in their individual, non-aggregated state, measured by transmission electron microscopy (TEM). As this value, 10 particles are randomly selected from those that can be clearly identified, and the maximum and minimum diameters of each particle are measured. The particle size of each particle is calculated as the average of its maximum and minimum diameters. The arithmetic mean of the particle sizes of these 10 particles is then taken as the primary particle size.
[0110] Furthermore, the purity of the alumina particles is preferably 99.5% or higher. By achieving this range, the abrasion resistance of the hard coating is improved.
[0111] From the viewpoint of balancing scratch resistance and transparency, the content of alumina particles relative to the total mass percentage of compounds (A), (B), and (C) of 100% is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more. Furthermore, the content of alumina particles is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 6% by mass or less. It can be 1% by mass or more and 10% by mass or less, 2% by mass or more and 8% by mass or less, or 3% by mass or more and 6% by mass or less.
[0112] The content of alumina particles relative to the total mass of the hard coating agent is preferably 0.1% by mass or more and 14% by mass or less, more preferably 0.5% by mass or more and 11% by mass or less, and even more preferably 1% by mass or more and 8% by mass or less.
[0113] [Other ingredients]
[0114] The hard coating and hard coating agent disclosed herein may contain organic solvents, resins, and additives as needed. Examples of additives include photopolymerization initiators, polymerization inhibitors, leveling agents, slip agents, defoamers, surfactants, antibacterial agents, antiblocking agents, plasticizers, ultraviolet absorbers, infrared absorbers, antioxidants, silane coupling agents, conductive agents, inorganic fillers other than alumina particles, pigments, dyes, etc.
[0115] [Photopolymerization initiator]
[0116] Hard coatings and hard coatings may contain photopolymerization initiators.
[0117] As photopolymerization initiators, various photopolymerization initiators can be used, such as monocarbonyl photopolymerization initiators, dicarbonyl photopolymerization initiators, acetophenone photopolymerization initiators, benzoin ether photopolymerization initiators, acylphosphine oxide photopolymerization initiators, and aminocarbonyl photopolymerization initiators. Photopolymerization initiators can be used in combination with sensitizers.
[0118] Examples include monocarbonyl photopolymerization initiators such as benzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, 2-isopropylthioxanthionone, 4-isopropylthioxanthionone, 2,4-diethylthioxanthionone, 2,4-dichlorothioxanthionone, and 1-chloro-4-propoxythioxanthionone; 2-ethylanthraquinone, 9,10-phenanthroquinone, and α-oxophenylethyl... Dicarbonyl photopolymerization initiators such as methyl esters; 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-hydroxycyclohexylphenyl ketone, diethoxyacetophenone, dibutoxyacetophenone, 2,2-dimethoxy-1,2-diphenylethane-1-one, 2,2-diethoxy-1,2-diphenylethane-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-methyl Acetophenone-based photoinitiators such as linopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butane-1-one, and 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime; benzoin ether-based photoinitiators such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and benzoin n-butyl ether; 2,4,6-trimethylbenzoyl diphenylphosphine oxide, 4-propylphenyl di(2,6-dichlorobenzoyl) Acylphosphine oxide photopolymerization initiators such as phosphine oxide; amino carbonyl photopolymerization initiators such as ethyl-4-(dimethylamino)benzoate, 2-butoxyethyl-4-(dimethylamino)benzoate, isopentyl-4-(dimethylamino)benzoate, 2-(dimethylamino)ethylbenzoate, 4,4'-bis-4-dimethylaminobenzophenone, 4,4'-bis-4-diethylaminobenzophenone, and 2,5'-bis(4-diethylaminobenzyl)cyclopentanone.
[0119] In particular, considering the resistance to yellowing after curing by active energy rays, acetophenone-based photopolymerization initiators such as 1-hydroxycyclohexylphenyl ketone are preferred.
[0120] Commercially available photopolymerization initiators include Omnirad 184 (trade name: 1-hydroxycyclohexylphenyl ketone), 651 (trade name: 2,2-dimethoxy-2-phenylacetophenone), 500 (trade name: a mixture of 50% 1-hydroxycyclohexylphenyl ketone and 50% benzophenone), 907 (trade name: 2-methyl-[4-(methylthio)phenyl]-2-morpholinopropane-1-one), and 127 (trade name: 2-hydroxy-1-(4-(4-(2-hydroxy-) 2-Methylpropionyl)benzoyl)phenyl)-2-methylpropane-1-one), 369 (2-benzyl-2-(dimethylamino)-4'-morpholinobutanone), 784 (trade name, bis(cyclopentadienyl)bis(2,6-difluoro-3-(1-pyrrole)phenyltitanium), 2959 (trade name, 1-(-4-(2-hydroxyethoxy)phenyl)-2-hydroxymethylacetone); Esacure One (trade name, oligomeric (2-hydroxymethyl-1-[4-(1-methylvinyl)phenyl]acetone) manufactured by DKSH Japan; Lucirin TPO (diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide) manufactured by BASF, etc.
[0121] From the viewpoint of hardness and scratch resistance, the content of the photopolymerization initiator relative to the total of 100 parts by mass of compounds (A), (B), and (C) is preferably 1 part by mass or more, more preferably 3 parts by mass or more. Furthermore, the content of the photopolymerization initiator relative to the total of 100 parts by mass of compounds (A), (B), and (C) is preferably 15 parts by mass or less, more preferably 10 parts by mass or less. It can be 1 part by mass or more and 15 parts by mass or less, or 3 parts by mass or more and 10 parts by mass or less.
[0122] [Example]
[0123] The present disclosure will now be described based on embodiments, but the present disclosure is not limited to these examples. It should be noted that, unless otherwise specified, “parts” and “%” in the embodiments represent “parts by mass” and “% by mass”, respectively.
[0124] <Methods for calculating the number-average molecular weight of polyisocyanates>
[0125] The number-average molecular weight of polyisocyanates with different molecular weight distributions was determined as follows. 1 g of polyisocyanate and 20 mL of 0.5 mol / L dibutylamine-toluene solution were added to a flask, diluted with 100 mL of acetone, and reacted at 25°C for 30 minutes. Then, titration was performed with 0.5 mol / L hydrochloric acid aqueous solution. A blank titration was also performed in the same manner, except that no polyisocyanate was added to the flask. The NCO% and number-average molecular weight were then calculated using the following formula.
[0126] NCO%={(Y1-X1)×0.5×42.02} / 1000×100
[0127] X1: The volume of aqueous hydrochloric acid solution required for titration of the solution containing polyisocyanate (mL)
[0128] Y1: The volume of aqueous hydrochloric acid solution required for titration of the blank solution containing no polyisocyanate (mL)
[0129] Number average molecular weight of polyisocyanate=(42.02×(NCO number) / (NCO%))×(non-volatile content)
[0130] ·NCO: Abbreviation for "isocyanate group"
[0131] ·42.02: Formula weight of NCO
[0132] ·NCO number: The number of NCO groups contained in one molecule of polyisocyanate
[0133] ·NCO%: The content rate (%) of NCO groups contained in one molecule of polyisocyanate
[0134] ·Non-volatile content: The content rate (%) of non-volatile components of the polyisocyanate
[0135] <Method for calculating the number average molecular weight of polyol>
[0136] Regarding the number average molecular weight of the polyol, the hydroxyl value is measured, and the number average molecular weight of the polyol is calculated by the following formula.
[0137] Number average molecular weight of polyol={[(hydroxyl value of polyol) / 1000] / 56.11 (molecular weight of potassium hydroxide)}×(number of hydroxyl groups in one molecule of polyol)
[0138] <Content rate of hydroxyl group-containing poly(meth)acrylate>
[0139] The content rate of the hydroxyl group-containing poly(meth)acrylate is calculated by the following formula.
[0140] Content rate (%) of hydroxyl group-containing polyacrylate=(hydroxyl value)×1000 / (molecular weight of potassium hydroxide)×(molecular weight of hydroxyl group-containing polyacrylate)×100
[0141]
[0142] For compounds such as urethane (meth)acrylates that can be determined by gel permeation chromatography (GPC), Mn and Mw were determined by GPC. A gel permeation chromatography system, Tosoh Corporation's "HLC-8220 GPC" (trade name), was used, with four separation columns connected in series: Tosoh Corporation's "TSK-GEL SUPER H5000", "TSK-GEL SUPER H4000", "TSK-GEL SUPER H3000", and "TSK-GEL SUPER H2000" (all trade names). Tetrahydrofuran was used as the mobile phase at 40°C, and the determination was performed at a flow rate of 0.6 ml / min. Mn and Mw were calculated using known polystyrene values.
[0143] <Methods for determining hydroxyl value>
[0144] Hydroxyl value (mg KOH / g) was determined using the potentiometric titration method specified in Japanese Industrial Standard JIS K0070:1992.
[0145] <Methods for determining acid value>
[0146] Acid value (mg KOH / g) was determined using the potentiometric titration method specified in Japanese Industrial Standard JIS K0070:1992.
[0147] <Synthesis of Compound (A)>
[0148] [Synthesis example A1]
[0149] In a four-necked flask equipped with a stirrer, reflux condenser, nitrogen inlet tube, thermometer, and dropping funnel, 669.6 parts by weight of isophorone diisocyanate (trade name VESTANAT IPDI, manufactured by EVONIK, NCO content 37.7%, molecular weight 223.2), 236.4 parts by weight of 1,6-hexanediol (manufactured by UBE, hydroxyl value 950 KOH mg / g, molecular weight 118.2), and 0.1 parts by weight of dioctyltin dilaurate (trade name Neostann U-810, manufactured by Nitto Kasei Corporation) were added. The mixture was heated to 80°C and reacted for 3 hours. The absorption peak (2250 cm⁻¹) from the isocyanate group (isocyanate ion) was confirmed by Fourier transform infrared spectroscopy (FT-IR). -1 The height of the solution was reduced to 1 / 6 of its initial value. Subsequently, 1049.0 parts by weight of dipentaerythritol pentaacrylate (trade name DPPA, manufactured by Molekula, molecular weight 524.5) were added, and the reaction was further carried out at 80°C for 3 hours. An absorption peak (2250 cm⁻¹) from the isocyanate group was confirmed in FT-IR. -1After the ions disappear, the temperature is lowered to 25°C to obtain a carbamate acrylate compound (a1-1) having 10 acryloyl groups (100% by mass of non-volatile components, 2000% by Mn).
[0150] <Synthesis of Compound (A)>
[0151] [Synthesis Example A2]
[0152] In a four-necked flask equipped with a stirrer, reflux condenser, nitrogen inlet tube, thermometer, and dropping funnel, 892.9 parts by weight of isophorone diisocyanate (trade name VESTANAT IPDI, manufactured by EVONIK, NCO content 37.7%, molecular weight 223.2), 432.6 parts by weight of 1,4-cyclohexanediethanol (trade name SKY CHDM, manufactured by Shin Nippon Rikka Co., Ltd., hydroxyl value 778 mgKOH / g, molecular weight 114.2), and 0.1 parts by weight of dioctyltin dilaurate (trade name Neostann U-810, manufactured by Nitto Kasei Corporation) were added. The mixture was heated to 80°C and reacted for 3 hours. The absorption peak (2250 cm⁻¹) from the isocyanate group (isocyanate ion) was confirmed by Fourier transform infrared spectroscopy (FT-IR). -1 The height of the solution was reduced to one-quarter of its initial value. Subsequently, 596.6 parts by weight of PE-3A (trade name, manufactured by THERMO FS, pentaerythritol triacrylate, 100% by weight, molecular weight 298.3) were added, and the reaction was further carried out at 80°C for 3 hours. An absorption peak (2250 cm⁻¹) from the isocyanate group was confirmed in FT-IR. -1 After the ions disappear, the temperature is lowered to 25°C to obtain a carbamate acrylate compound (a1-2) having 6 acryloyl groups (100% by mass of non-volatile components, Mn 1900).
[0153] <Compound A>
[0154] • Compound (a1-1): Carbamate acrylate (a1-1) (Synthetic example A1, 10 acryloyl groups, Mn2000)
[0155] • Compound (a1-2): Carbamate acrylate (a1-2) (Synthetic example A2, 6 acryloyl groups, Mn1900)
[0156] Compound (a2-1): Dipentaerythritol hexaacrylate (a2-1) (DPHA, 6 acryloyl groups, formula weight 578)
[0157] <Compound B>
[0158] • Compound (b1): HBA (abbreviation, 4-hydroxybutyl acrylate, manufactured by Mitsubishi Chemical Corporation)
[0159] • Compound (b2): HPA (abbreviation, hydroxypropyl acrylate, manufactured by Osaka Organic Chemical Industry Co., Ltd.)
[0160] Compound (b3): ACMO (abbreviation, acryloylmorpholine, manufactured by KJ Chemicals)
[0161] <Compound C>
[0162] ·MAC-SQ HDM (trade name, manufactured by Toa Synthetic Co., Ltd., a 50% concentration of non-volatile component of a compound (c1) having a silsesquioxane backbone and a methacrylamide group, manufactured by Toa Synthetic Co., Ltd.)
[0163] • AC-SQ SI20 (trade name, manufactured by Toa Synthetic Co., Ltd., a compound having a silsesquioxane skeleton and an acryloyl group (c2))
[0164] SR-13 (trade name, manufactured by Konishi Chemical Industry Co., Ltd., a sesquioxane skeleton compound (c3) without (meth)acryloyl groups)
[0165] <Compound D> Acrylate compounds with 2 to 5 acryloyl groups (D)
[0166] M 315: Aronix M315 (trade name, manufactured by Dong-A Synthetic Co., Ltd., hydroxyl value 12 mg KOH / g, a mixture of 92% by mass of ethylene oxide-modified triacrylate isocyanurate (compound d1) (formula 423) and 8% by mass of ethylene oxide-modified diacrylate isocyanurate (compound d2) (formula 369)).
[0167] <Alumina particles>
[0168] KT-110 AL (trade name, manufactured by TOYOCHEM), a 35% concentration of non-volatile components of alumina particles in a MEK (methyl ethyl ketone) / cyclohexanone aliphatic solvent dispersion.
[0169] Photopolymerization initiators
[0170] Omnirad 184 (1-hydroxycyclohexylphenyl ketone, acetophenone-based photopolymerization initiator, manufactured by IGM Corporation)
[0171] Solvent
[0172] •PGM (Propylene Glycol Monomethyl Ether, manufactured by Daishin Chemical Co., Ltd.)
[0173] [Acrylic substrate]
[0174] An acrylic-based matrix is prepared using granules made from copolymers synthesized by the method described below, or commercially available granules, with a peak tanδ temperature of 125°C or higher and 160°C or lower. It should be noted that the peak tanδ temperature is determined by measuring tanδ at a frequency of 0.1 Hz using a DMA measuring instrument (DMS6100 (Hitachi High Technology Co., Ltd.)) according to JIS K 7244-4.
[0175] Granules of methyl methacrylate copolymers (N-1), (N-5) and (N-7), and their film formation, are manufactured according to the method described in Japanese Patent Application Publication No. 2009-52036.
[0176] Manufacturing of Methyl Methacrylate Copolymer (N-1) Granules
[0177] 20 parts methyl methacrylate, 80 parts acrylamide, 0.3 parts potassium persulfate, and 1500 parts deionized water were added to a reactor, and the reactor was maintained at 70°C while being purged with nitrogen. The reaction continued until the monomers were completely converted into polymers, yielding an aqueous solution of the methyl methacrylate / acrylamide copolymer. This aqueous solution was used as a suspending agent. A solution containing 0.05 parts by mass of the above suspending agent dissolved in 165 parts by mass of deionized water was supplied to a stainless steel autoclave equipped with baffles and a three-bladed swept-back (Pfaudler type) stirrer, and the system was stirred at 400 rpm while being purged with nitrogen. Then, while stirring the reaction system, the following mixture (L-1) was added, and the temperature was raised to 70°C. The moment the internal temperature reached 70°C was taken as the start of polymerization, which was maintained for 180 minutes to end the polymerization. Afterward, bead-like copolymers (N-1) were obtained according to conventional methods. The polymerization rate of this copolymer (N-1) was 98%.
[0178] <Mixture (L-1)>
[0179] 5 parts by weight of α-methylene-γ-butyrolactone
[0180] 95 parts by weight of methyl methacrylate
[0181] 0.6 parts by weight of n-dodecyl mercaptan
[0182] 0.4 parts by weight of lauryl peroxide
[0183] The obtained bead-like copolymer (N-1) was compounded using a twin-screw extruder (TEX25αIII-52.5CW-4V (manufactured by Nippon Steel Corporation, L / D=52.5)) at a barrel temperature of 280°C and a screw speed of 100 rpm to obtain copolymer (N-1) granules. 1H-NMR analysis of the obtained granules revealed that they contained 5% by mass of α-methylene-γ-butyrolactone (MBL) units and 95% by mass of methyl methacrylate (MMA) units. The Mw, determined by GPC, was 115,000, and the Tg, determined by DSC, was 112 °C.
[0184] <Film Formation of Methyl Methacrylate Copolymer (N-1) Granules (Preparation of Acrylic Substrate (P-1))>
[0185] The granules of the copolymer (N-1) obtained above were fed into a biaxial melt-mixing mill (HK-25D, manufactured by Parker Corporation) with a T-die and adjusted to a die lip spacing of 0.6 mm, and melt-forming was performed at a temperature of 242°C. The roller temperature was set to 130°C, and the winding speed was adjusted to obtain a film with a thickness of approximately 80 μm. The obtained film was fed into an automatic biaxial stretching device (IMC-11A9, manufactured by Imoto Manufacturing Co., Ltd.) and subjected to 1.5 times simultaneous biaxial stretching at a temperature of 122°C to obtain an acrylic substrate (P-1) with a thickness of 40 μm. The peak temperature of tanδ, determined based on DMA, was 127°C.
[0186] Acrylic-based substrate (P-2)
[0187] Acryviewa TRM-Z-100 (granules, glass transition temperature 122°C) manufactured by Nippon Shokubai Co., Ltd. was used as the granule for methyl methacrylate copolymer (N-2), and film formation was carried out in the same manner as the film formation of the above granules to obtain an acrylic substrate (P-2) with a thickness of 40 μm. The peak temperature of tanδ measured based on DMA was 136°C.
[0188] Acrylic-based substrate (P-3)
[0189] Acryviewa TRM-250 (granules, glass transition temperature 130°C) manufactured by Nippon Shokubai Co., Ltd. was used as the granule for methyl methacrylate copolymer (N-3). Film formation was carried out in the same manner as the film formation of the above granules to obtain an acrylic substrate (P-3) with a thickness of 40 μm. The peak temperature of tanδ measured based on DMA was 145°C.
[0190] Acrylic substrate (P-4)
[0191] A 40 μm thick film, "PU-H403" from Longhua, was used directly as a methyl methacrylate copolymer film (P-4). The peak temperature of tanδ, determined based on DMA, was 145 °C.
[0192] Manufacturing of Methyl Methacrylate Copolymer (N-5) Granules
[0193] The mixture (L-1) was changed to a mixture (L-5) consisting of the following components, and the same procedure as the production of the copolymer (N-1) granules was followed to obtain methyl methacrylate copolymer (N-5) granules. 1 Compositional analysis by ¹H-NMR showed that MBL units were 50% by mass and MMA units were 50% by mass. The Mw determined by GPC was 115,000, and the glass transition temperature determined by DSC was 141 °C.
[0194] <Mixture (L-5)>
[0195] 50 parts by weight of α-methylene-γ-butyrolactone
[0196] 50 parts by weight of methyl methacrylate
[0197] 0.6 parts by weight of n-dodecyl mercaptan
[0198] 0.4 parts by weight of lauryl peroxide
[0199] <Film Formation of Methyl Methacrylate Copolymer (N-5) Granules (Preparation of Acrylic Substrate (P-5))>
[0200] The copolymer (N-1) granules were changed to copolymer (N-5) granules. Otherwise, the granules were film-formed in the same way as the granules above, to obtain an acrylic substrate (P-5) with a thickness of 40 μm.
[0201] The peak temperature of tanδ, as determined by DMA, is 155℃.
[0202] Acrylic-based substrate (P-6)
[0203] DIANAAL BR85 (granules, glass transition temperature 105°C) manufactured by Mitsubishi Chemical Corporation was used as the granule for methyl methacrylate copolymer (N-6), and film formation was carried out in the same manner as the film formation of the above granules to obtain an acrylic substrate (P-6) with a thickness of 40 μm. The peak temperature of tanδ, measured based on DMA, was 118°C.
[0204] Manufacturing of Methyl Methacrylate Copolymer (N-7) Granules
[0205] The mixture (L-1) was changed to a mixture (L-7) consisting of the following components, and otherwise the same procedure as the production of polymer (N-1) granules was carried out to obtain methyl methacrylate copolymer (N-7) granules. 1H-NMR compositional analysis revealed that the α-methylene-γ-butyrolactone (MBL) unit was 60% by mass, the methyl methacrylate unit was 40% by mass, the Mw (based on GPC) was 116,000, and the glass transition temperature (based on DSC) was 152 °C.
[0206] <Mixture (L-7)>
[0207] 65 parts by weight of α-methylene-γ-butyrolactone
[0208] 35 parts by weight of methyl methacrylate
[0209] 0.6 parts by weight of n-dodecyl mercaptan
[0210] 0.4 parts by weight of lauryl peroxide
[0211] <Filming of methyl methacrylate copolymer (N-7) (Preparation of acrylic substrate (P-7))>
[0212] The copolymer (N-1) granules were changed to copolymer (N-7) granules, and film formation was performed in the same manner as the above-mentioned granule film formation to obtain an acrylic substrate (P-7) with a thickness of 40 μm. The peak temperature of tanδ, measured based on DMA, was 169 °C.
[0213] [Table 1]
[0214]
[0215] Footnotes in Table 1
[0216] 1) α-Methylene-γ-butyrolactone unit
[0217] 2) Methyl methacrylate unit
[0218] 4) Tg of granules based on DSC
[0219] 5) Stretch film obtained using an automatic biaxial stretching device
[0220] 6) Peak temperature of tanδ of DMA-based stretched films
[0221] 7) Longhua Company's "PU-H403" film
[0222] <Preparation of Hard Coating>
[0223] [Example 1]
[0224] 10 parts of compound (a1-1), 30 parts of compound (a2-1), 50 parts of compound (b1), 20 parts of MAC-SQ HDM (manufactured by Toa Synthetic Co., Ltd., a propylene glycol monobutyl ether solution with a non-volatile component concentration of 50% of methacryloyl silsesquioxane (C1)) (converted to 10 parts of solid component), and 8 parts of Omnirad 184 (manufactured by IGM Corporation) as a photopolymerization initiator were thoroughly mixed, and the propylene glycol monoethyl ether as an organic solvent was adjusted to a non-volatile component concentration of 60% to obtain hard coating agent S1.
[0225] The Creation of Layer R1
[0226] On a 40 μm thick acrylic substrate (P-4) (PU-H403, manufactured by Longhua Corporation), the aforementioned hard coating S1 was applied using a rod coater to achieve a dried film thickness of 5 μm, and then dried at 80°C for 1 minute. Next, it was heated by a high-pressure mercury lamp at 200 mJ / cm². 2 Two ultraviolet irradiations are performed to form a hard coating, and a laminate R1 is fabricated.
[0227] [Example 2]
[0228] 40 parts of compound (a2-1), 50 parts of compound (b1), 20 parts of MAC-SQ HDM (manufactured by Toa Synthetic Co., Ltd., a propylene glycol monobutyl ether solution with a non-volatile component concentration of 50% of methacryloyl silsesquioxane (c1)) (10 parts of solid component), 14.3 parts of KT-110AL (manufactured by TOYOCHEM Co., Ltd., a MEK / cyclohexanone aliphatic solvent dispersion with a non-volatile component concentration of 35% of alumina particles) (5 parts of solid component), and 8 parts of Omnirad 184 (manufactured by IGM Co., Ltd.) as a photopolymerization initiator were thoroughly mixed, and the propylene glycol monoethyl ether as an organic solvent was adjusted to a non-volatile component concentration of 60% to obtain hard coating agent S2.
[0229] Creating Layer R2
[0230] The hard coating S2 obtained above was processed in the same manner as in Example 1 to produce a laminate R2.
[0231] [Examples 3-30][Comparative Examples 1-6]
[0232] As shown in Tables 2-6, the materials, formulation amounts, and substrates were changed, but otherwise the same procedure was followed as in Example 1 to produce hard coatings S3-36, laminates R3-R30, and laminates RR1-RR6.
[0233] <Evaluation Items>
[0234] (Seamless fit)
[0235] A tape adhesion test was conducted using the fabricated laminate. The tape adhesion test was performed in accordance with JIS K5600-5-6 (1999 edition).
[0236] A total of 100 cells were created by slicing the laminate with 10 cells x 10 cells spaced 1 mm apart. The slits were cut to a depth reaching the substrate but not cutting through it. Transparent tape (25 mm wide, made by NICHIBAN) was then applied to the coating surface and quickly peeled off by hand. The state of the remaining cells was then observed. The evaluation results were based on the following evaluation criteria.
[0237] Evaluation Criteria
[0238] AA: No peeling (0 peeled cells) (Very good).
[0239] A: Peeling was observed at 1 to 3 bars (good).
[0240] B: Observed peeling of 4 or more but less than 6 squares (no practical problem).
[0241] C: Observed peeling of more than 7 squares (not usable).
[0242] (Pencil hardness)
[0243] Using the fabricated laminate, according to JIS K5600-5-4 (1999 edition), pencils of various hardnesses were placed at a 45° angle on the surface of the hard coating of the laminate, and a scratch test was conducted under load. The evaluation results were based on the following evaluation criteria.
[0244] Evaluation Criteria
[0245] A: 2H or above (Good).
[0246] B: H or higher and less than 2H (no practical problem).
[0247] C: Below H (not practical).
[0248] (Abrasion resistance)
[0249] The abrasion resistance of the fabricated laminate was evaluated using a "Vibration-Modulated Friction Fastness Tester" manufactured by Tester Industries. Friction components (surface area 4 cm²) were subjected to a 500g load. 2 Install steel wool #0000 on the surface of the hard coating (2cm x 15cm) and repeat 10 times. Then, count the number of scratches on the surface of the hard coating and evaluate according to the following criteria. The fewer the number of scratches, the better; if there are 9 or fewer, it can be used without any practical problems.
[0250] Evaluation Criteria
[0251] AA: No scratches (Excellent)
[0252] A: 1 to 3 scratches (Good)
[0253] B: 4 to 9 scratches (no practical problems)
[0254] C: More than 10 scratches (unusable)
[0255] (Interference fringes)
[0256] The fabricated laminate was cut into 5cm x 5cm pieces. The entire surface of the acrylic film substrate, opposite to the coating surface, was rubbed approximately 10 times in a circular motion with waterproof paper #1000. Then, black Magic Ink (registered trademark) replenishment solution (manufactured by Teranishi Chemical Industry Co., Ltd.) was applied and dried at 70°C for 2 minutes. The absolute reflectance at 5° was measured in the wavelength range of 380–780 nm using a spectrophotometer (manufactured by Hitachi High Technology Co., Ltd., model: U-4100). Five large-amplitude ripples were selected from the reflectance curve, and their average value was defined as the ripple size. The ripple size was calculated based on the following formula.
[0257] R = Rmax - Rmin
[0258] R: Size of the ripples
[0259] Rmax: Maximum value of the ripple.
[0260] Rmin: Minimum value of ripple
[0261] Evaluation Criteria
[0262] AA: The ripple size is below 0.2% (very good).
[0263] A: The ripple size is above 0.3% and below 0.5% (good).
[0264] B: The ripple size is above 0.6% and below 0.8% (no practical problems).
[0265] C: The ripple size is above 0.9% (not practical).
[0266] (Seam tightness after thermal cycling test)
[0267] Using the fabricated laminate, long-term stability (thermal cycling) tests were conducted using the ESPEC TSE-11-A miniature thermal shock apparatus. Specifically, for the surface of the hard coating after 200 cycles of exposure at -40°C, 100°C, and 40 minutes each, the same (adhesion) evaluation method as described above was used, and the evaluation was based on the following evaluation criteria.
[0268] Evaluation Criteria
[0269] AA: No peeling (0 peeled cells) (Very good).
[0270] A: Peeling was observed at 1 to 3 bars (good).
[0271] B: Observed peeling of 4 or more but less than 6 squares (no practical problem).
[0272] C: Observed peeling of more than 7 squares (not usable).
[0273] [Table 2]
[0274]
[0275] [Table 3]
[0276]
[0277] [Table 4]
[0278]
[0279] [Table 5]
[0280]
[0281] [Table 6]
[0282]
[0283] The present invention has been described with reference to the above-described embodiments, but the present invention is not limited to the above-described embodiments. Various modifications can be made to the structure and details of the present invention within the scope of the present invention.
[0284] The disclosures of this application are related to the subject matter described in Japanese Patent Application No. 2025-277340 filed on December 23, 2025, and Japanese Patent Application No. 2026-016761 filed on February 4, 2026, the entire disclosures of which are incorporated herein by reference.
Claims
1. A laminate comprising a substrate and a hard coating, The substrate is an acrylic substrate with a peak temperature of tanδ above 125°C and below 160°C, obtained by dynamic viscoelasticity measurement at a frequency of 0.1 Hz. The hard coating is formed by a hard coating agent comprising a compound (A) having six or more (meth)acryloyl groups, a compound (B) having one olefinic unsaturated group, and a compound (C) having a sesquioxane skeleton.
2. The laminated body according to claim 1, wherein, The compound (B) is a compound having one (meth)acryloyl group.
3. The laminated body according to claim 1, wherein, The compound (B) is a compound having one olefinic unsaturated group and a hydroxyl group.
4. The laminate according to claim 1 or 2, wherein, The compound (A) comprises a carbamate (meth)acrylate (a1) having more than 6 (meth)acryloyl groups.
5. The laminate according to claim 1 or 2, wherein, The hard coating also contains alumina particles.
6. The laminate according to claim 1 or 2, wherein, The content of compound (A) is 20% by mass and less than 55% by mass in the total of 100% by mass of compounds (A), (B), and (C). The content of compound (B) is 35% by mass and less than 70% by mass in the total of 100% by mass of compounds (A), (B), and (C). The content of compound (C) is more than 1% by mass and less than 30% by mass in the total of 100% by mass of compounds (A), (B) and (C).
7. A hard coating agent comprising a compound (A) having six or more (meth)acryloyl groups, a compound (B) having one olefinically unsaturated group, and a compound (C) having a silsesquioxane skeleton. The compound (A) is a carbamate (meth)acrylate having more than 6 (meth)acryloyl groups. The compound (B) is a compound having one (meth)acryloyl group.
8. A hard coating agent comprising a compound (A) having six or more (meth)acryloyl groups, a compound (B) having one olefinically unsaturated group, and a compound (C) having a silsesquioxane skeleton. The compound (A) is a carbamate (meth)acrylate having more than 6 (meth)acryloyl groups. The compound (B) is a compound having one olefinic unsaturated group and a hydroxyl group.
9. The hardening agent according to claim 7 or 8, wherein, The content of compound (A) is 20% or more and 55% or less in the total of 100% by mass of compounds (A), (B) and (C).
10. The hardening agent according to claim 7 or 8, wherein, The content of compound (B) is 40% by mass or more in the total 100% by mass of compounds (A), (B) and (C).
11. The hardening agent according to claim 7 or 8, wherein, The content of compound (C) is more than 1% by mass and less than 30% by mass in the total of 100% by mass of compounds (A), (B) and (C).
12. The hardening agent according to claim 7 or 8, wherein, The content of compound (A) is 20% by mass and less than 55% by mass in the total of 100% by mass of compounds (A), (B), and (C). The content of compound (B) is 35% by mass and less than 70% by mass in the total of 100% by mass of compounds (A), (B), and (C). The content of compound (C) is more than 1% by mass and less than 30% by mass in the total of 100% by mass of compounds (A), (B) and (C).
13. The hard coating agent according to claim 7 or 8, used to form a hard coating in a laminate having an acrylic substrate and a hard coating, wherein the temperature at the peak of tanδ obtained by dynamic viscoelasticity measurement at a measurement frequency of 0.1 Hz is 125°C or higher and 160°C or lower.
Citation Information
Patent Citations
Acrylic based film, lamination film, and polarization plate
JP2009052036A
Acrylic film for UV imprint, laminate thereof, and method of manufacturing acrylic film for UV imprint
JP2010196026A
Film
JP2013137485A
Remote real system such as a virtual houseboat
JP2026016761A
Actinic-ray-curable resin composition, cured object, layered product, and article
WO2020209264A1